ANALISIS PERBANDINGAN FUNGSI DAN MAKNA SEMIOTIK MOTIF PHOENIX PAKAIAN TRADISIONAL WANITA TIONGKOK QIPAO DI MASA DINASTI QING DAN MASA GENERASI Z DI SURABAYA - Yuria, Vella; Leonardo, Ong Peter (Universitas Widya Kartika Surabaya, 2024)
This research discusses the function of qipao and the meaning of the Phoenix symbol on qipao during the Qing Dynasty and Generation Z. Qipao is a traditional Chinese garment often adorned with Phoenix motifs, which are mythological creatures in Chinese culture. In this context, the research explores the evolution of qipao and the use of the Phoenix symbol from the Qing Dynasty to Generation Z, the current young generation. In this study, the author used a qualitative method consisting of literature review and interviews to compare the changes in qipao and the symbolic meaning of the Phoenix in qipao between two different time periods. This analysis includes social, cultural, and historical factors that influence the evolution of the Phoenix's meaning in the design and use of qipao. The results of this research are expected to provide deeper insights into the differences in qipao and the symbolic meaning of the Phoenix motif in qipao.